The views of African and Middle Eastern Gastroenterologists on the management of mild-to-moderate, non-erosive gastro-esophageal reflux disease (GERD). (4th March 2022) - Al-Marhabi, Ahmed; Hashem, Ahmed; Zuberi, Bader Faiyaz; Onyekwere, Charles; Lodhi, Imran; Mounir, Mohamed; Alkhowaiter, Saad; Al Awadhi, Sameer; Naidoo, Vasudevan G.; Hamada, Yasser
ABSTRACT: Introduction: Gastro-esophageal reflux disease (GERD) is a common gastrointestinal disorder that occurs when backflow of the gastric contents into the esophagus results in troublesome symptoms. Though GERD has been extensively studied in Western populations, literature on the management of GERD in patients in Africa and Middle East (AME) is scarce. Areas covered: In this review, we provide an overview of the management of mild-to-moderate GERD in AME. Here we focus on the efficacy and safety of currently available treatments for GERD to help physicians and community pharmacists appropriately manage patients with mild-to-moderate GERD in the primary healthcare setting, detailing specific situations and patient scenarios that are relevant to the region, including management of GERD during Ramadan and post-bariatric surgery. Expert opinion: Under-appreciation of the burden of GERD in the region has resulted in a lack of consensus on management. Barriers that currently prevent the adoption of treatment guidelines in the primary healthcare setting may include lack of availability of local guidelines and referral systems, a paucity of region-specific research, and dogmatic adherence to traditional practice. By increasing awareness, strengthening knowledge, and by more effective utilization of resources, physicians and pharmacists could optimize GERD management strategies to better support patients.